Analysis of Delay Factors in EPC Power Plant Projects (Case Study: PLTMG Project in Sumbawa) - Maulana Indra Gunawan; Hendy Suryana; Oviyan Patra; Evan Nugraha (Journal Research of Social Science, Economics, and Management, 2025)
Construction projects often face the risk of delays, which can affect cost, quality, and schedule performance. This research aims to analyze the factors causing delays in the Engineering, Procurement, and Construction (EPC) Gas Engine Power Plant (PLTMG) project in Sumbawa and to formulate improvement recommendations. The research employs the Partial Least Squares – Structural Equation Modeling (PLS-SEM) method with 67 respondents consisting of the project owner, contractor, and supervision consultant. The research variables include design, financial, resources, contractor, material, external, and owner as independent variables and time overrun as the dependent variable. The results show that the external factor has a positive and significant influence on project delays (? = 0.534; p = 0.000), which includes regulatory changes, extreme weather, permit delays, and socio-cultural influences. The owner factor shows a nearly significant effect (p = 0.092), while design, financial, contractor, material, and resource factors have no significant impact. The research model demonstrates good predictive capability (R² = 0.696; Q² = 0.516). Improvement recommendations focus on mitigating external factors, including establishing a legal team to monitor regulations, developing a flexible work schedule adapted to weather conditions, expediting permits through a dedicated liaison officer, and enhancing communication with the local community. These findings are expected to serve as a reference for stakeholders in managing delay risks in similar construction projects.